2013
DOI: 10.1364/ao.52.007867
|View full text |Cite
|
Sign up to set email alerts
|

Underwater optical wireless communications: depth dependent variations in attenuation

Abstract: Depth variations in the attenuation coefficient for light in the ocean were calculated using a one-parameter model based on the chlorophyll-a concentration C c and experimentally-determined Gaussian chlorophylldepth profiles. The depth profiles were related to surface chlorophyll levels for the range 0-4 mg∕m 2 , representing clear, open ocean. The depth where C c became negligible was calculated to be shallower for places of high surface chlorophyll; 111.5 m for surface chlorophyll 0.8 < C c < 2.2 mg∕m 3 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(49 citation statements)
references
References 11 publications
0
49
0
Order By: Relevance
“…Extending from the sea surface to the bottom, the chlorophyll variation curve is observed to follow a skewed Gaussian profile [53]. Accordingly, the attenuation coefficient has shown to start from 0.05 m −1 and reaches the peak record 0.1 m −1 around 100 m depth, which starts decreasing for deeper waters [52]. b) Oceanic turbulence: Oceanic turbulence is defined as the rapid variations in the refraction index due to fluctuations in the aquatic medium parameters such as pressure, density, salinity, temperature, etc.…”
Section: B Underwater Propagation Characteristics Of Optical Wavesmentioning
confidence: 96%
See 2 more Smart Citations
“…Extending from the sea surface to the bottom, the chlorophyll variation curve is observed to follow a skewed Gaussian profile [53]. Accordingly, the attenuation coefficient has shown to start from 0.05 m −1 and reaches the peak record 0.1 m −1 around 100 m depth, which starts decreasing for deeper waters [52]. b) Oceanic turbulence: Oceanic turbulence is defined as the rapid variations in the refraction index due to fluctuations in the aquatic medium parameters such as pressure, density, salinity, temperature, etc.…”
Section: B Underwater Propagation Characteristics Of Optical Wavesmentioning
confidence: 96%
“…Despite all these appealing virtues, there exist many challenges to implement UOWC systems in practice: Firstly, [52], and oceanic turbulence [80]. Secondly, even if the carrier wavelength of the light beam is chosen to be blue or green in order to mitigate the underwater attenuation effects [18], [19], [81], light beam propagation still undergoes absorption, scattering, and thus multipath fading because of the interactions of water molecules and particulates with the photons [75], [76].…”
Section: A Waves Under the Sea: A Tour Of The Underwater Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of this research, the former is not suitable, as it omits pressure changes. The downside of using the latter [12] is that the range of wavelengths considered only goes from 500 nm, whereas previous research has shown ideal wavelengths for optical wireless links in open ocean to be 430-490 nm [3]. Figure 3 gives an example of a refractive index profile obtained using the empirical equations in [12]; a data set from the Pacific Ocean was used [13], and the refractive index calculated down to 3000 m with a set wavelength of 500 nm.…”
Section: Refractive Profilementioning
confidence: 99%
“…In the underwater domain, previous studies have shown how slight variations in the composition of seawater leads to local changes in attenuation (or energy loss) [1,2]; recently, these ideas have been used to determine the attenuation as a function of depth [3]. While the study in [3] accurately describes the communication channel for links where the receiver is directly below or above the transmitter, the directional properties of the beam must be considered for links that are neither perpendicular nor parallel to the ocean surface. This is because it is possible at these orientations for directional changes to occur as the transmitted light beam undergoes multiple refractions.…”
Section: Introductionmentioning
confidence: 99%